Laminated sheet and method for manufacturing the same

By using a laminated sheet structure containing synthetic paper substrate and self-adhesive layer, the problems of complex preparation and printing difficulties in the prior art are solved, and simple and diverse printing and clear visible information display are achieved, suitable for small batch production and transparent material adhesion.

JP2025018325APending Publication Date: 2025-02-06YUPO CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023121925
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

In the prior art, when preparing laminated sheets with adhesion surfaces, there are problems such as complex processes, unsuitable for small batch diversification production, and inability to efficiently print on opaque adhesive layers, and the adhesion of the adhesive layer leads to problems with laminated sheet adhesion equipment.

Method used

Using a laminated sheet structure containing a synthetic paper substrate and a self-adhesive layer, the self-adhesive layer is a foam layer and does not contain a silicone resin or a fluorocarbon resin release agent layer, by printing visible information on the release sheet and transferring it to the self-adhesive layer, using ethylene-vinyl acetate copolymer or (meth)acrylate copolymer as the adhesive material, and printing is performed by photocuring or low boiling solvent-dried ink.

Benefits of technology

It realizes simple preparation of laminated sheets, is suitable for diversified printing, supports small batch and diversified production, and can clearly display the adhesion surface information, avoid adhesion equipment problems, and improves printing efficiency and visible information transfer effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018325000001_ABST
    Figure 2025018325000001_ABST
Patent Text Reader

Abstract

To provide a laminated sheet in which a laminated sheet equipped with a sticking surface can be easily manufactured, and a visible information can be clearly printed on the sticking surface, and a method for manufacturing the sheet.SOLUTION: A laminated sheet comprises a sticking sheet including a synthetic paper substrate and a self-adsorbing layer, and a release sheet, where the self-adsorbing layer and the release sheet are directly in contact with each other, the release sheet does not have a release agent layer containing silicone-based resin or fluorine-based resin on a surface on the self-adsorbing layer side, and the self-adsorbing layer is configured to have visible information on a surface on the release sheet side.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate sheet and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art In recent years, laminated sheets having an adhesive surface that is adhered to an adherend such as a smooth transparent member such as window glass have come into widespread use (see Patent Document 1).

[0003] Here, when the adhesive surface of the laminate sheet is attached to a transparent member, not only the front side of the laminate sheet but also the back side of the laminate sheet, i.e., the adhesive surface, can be seen through the transparent member. Therefore, there is a need to print visible information such as characters or patterns on the adsorption layer, adhesive layer, adhesive layer, or the like provided on the adhesive surface.

[0004] In addition, a method for manufacturing a laminated sheet having such an adhesive surface includes, for example, a method in which a highly transparent adhesive layer (adhesive layer) is provided after printing on the surface of the base material in advance. However, when changing the pattern to be printed, application of the adhesive must be interrupted in a later process, and this method is not suitable for on-demand printing corresponding to small-lot, high-mix production. In addition, this method cannot be applied to laminated sheets having an opaque adhesive layer, such as the suction sheet described in Patent Document 1.

[0005] On the other hand, when printing directly onto the adhesive layer, problems occur such as the tack (stickiness, adhesion) of the adhesive layer causing the laminated sheet to stick inside the printing device. To address this problem, for example, providing a microstructure on the surface of the adhesive layer (Patent Document 2) or using a UV-curable resin (Patent Document 3) have been proposed.

[0006] Also proposed is a method of forming a pattern using a pressure-sensitive adhesive ink containing a colorant between the substrate and the adhesive layer, rather than on the surface of the adhesive layer (Patent Document 4).

[0007] As another method, a method has been proposed in which decorative printing is performed on a release sheet in advance, and then this is attached to an adhesive layer to transfer the printed portion onto the surface of the adhesive layer (Patent Document 5). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2018 / 151274 [Patent Document 2] Patent Publication No. 2021-95547 [Patent Document 3] Patent Publication No. 2017-62430 [Patent Document 4] Japanese Patent Publication No. 4-85383 [Patent Document 5] Patent No. 5752292 Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the methods described in Patent Documents 2 to 4, the manufacturing process of the laminated sheet having an adhesive surface becomes complicated. In addition, in the method described in Patent Document 4, the printing ink that can be used is limited, making it difficult to respond to printing for various purposes. In addition, in the method described in Patent Document 5, for example, a thin film layer (release agent layer) containing a release agent containing a silicone resin, a fluorine resin, etc. is formed on the surface of the release sheet, such as a release processing layer. Therefore, when printing is performed on the release sheet, the release agent layer formed between the release sheet and the printing layer gets in the way, making it difficult to perform clear printing on the surface of the release sheet.

[0010] The present invention aims to solve the above problems. That is, the object of the present invention is to provide a laminated sheet having an adhesive surface that is easy to prepare, suitable for printing for various applications, and further, by clearly printing on the surface of the release sheet, visible information can be clearly confirmed on the adhesive surface (to be transferred later), and a method for producing the same.

[0011] The present inventors have developed a laminated sheet including an adhesive sheet including a synthetic paper base material (synthetic paper base material) and a self-adhesive layer, and a release sheet, the synthetic paper base material, the self-adhesive layer, and the release sheet being arranged in this order, and the release sheet not having a release agent layer including a silicone resin or a fluorine resin. They have also found that by using the laminated sheet, visible information printed on the release sheet can be clearly and easily transferred to the adhesive surface of the self-adhesive layer, and have arrived at the present invention.

[0012] That is, the present invention provides various specific embodiments as shown below. [1] A laminated sheet comprising an adhesive sheet including a synthetic paper base material and a self-adhesive layer, and a release sheet, wherein the self-adhesive layer and the release sheet are in direct contact with each other, the release sheet does not have a release agent layer containing a silicone-based resin or a fluorine-based resin on the surface facing the self-adhesive layer, and the self-adhesive layer is configured to have visible information on the surface facing the release sheet. Here, "visible information" refers to a type of information, i.e., visual information that can be seen and grasped with the naked eye, and the laminate sheet of the present invention may have an appearance in which the visible information on the surface of the self-adhesive layer is covered by a release sheet and cannot be seen.

[0013] [2] The laminate sheet according to [1] above, wherein the self-adhesive layer is a foam layer.

[0014] [3] The laminate sheet according to the above [2], wherein the foam layer contains an ethylene-vinyl acetate copolymer or a (meth)acrylic acid ester copolymer.

[0015] [4] The laminate sheet according to any one of the above [1] to [3], wherein the release sheet is a thermoplastic resin sheet made of a polyolefin resin or a polyester resin.

[0016] [5] preparing an adhesive sheet comprising a synthetic paper substrate and a self-adhesive layer; printing visible information on the surface of the release sheet that does not have a release agent layer containing a silicone-based resin or a fluorine-based resin; A method for manufacturing a laminated sheet, comprising a step of bonding the release sheet and the adhesive sheet so that the visible information printed surface of the release sheet faces the self-adhesive layer of the adhesive sheet, thereby transferring visible information to the self-adhesive layer.

[0017] [6] The step of preparing the adhesive sheet comprises: applying a self-adhesive layer-forming composition to a surface of the synthetic paper base material; and a step of crosslinking the self-adhesive layer-forming composition after foaming the composition. The manufacturing method described in [5] above. Effect of the Invention

[0018] According to the present invention, it is possible to provide a laminated sheet having an adhesive surface that is easy to prepare, suitable for printing for various purposes, and by clearly printing on the surface of the release sheet, visible information can be clearly confirmed on the adhesive surface (to be transferred later), and a method for producing the same. In addition, since the visible information can be quickly changed, it is possible to respond to small-lot, high-mix production such as on-demand printing. [Brief description of the drawings]

[0019] [Figure 1] 2 is a flowchart illustrating an example of a method for producing a laminate sheet according to the present invention. [Diagram 2] 4 is an example of visible information printed on the release sheet according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention will be described in detail.

[0021] (Laminated sheet) The laminated sheet of the present invention comprises an adhesive sheet including a synthetic paper base material and a self-adhesive layer, and a release sheet. Here, the self-adhesive layer and the release sheet are in direct contact with each other, and the release sheet does not have a release agent layer including a silicone-based resin or a fluorine-based resin on the surface of the self-adhesive layer side. The self-adhesive layer is configured to have visible information on the surface of the release sheet side. From the viewpoint of adsorption, the self-adhesive layer is preferably a foamed layer. From the same viewpoint, the self-adhesive layer preferably includes an ethylene-vinyl acetate copolymer or a (meth)acrylic acid ester copolymer. From the viewpoint of releasability and adhesion, the release sheet is preferably a thermoplastic resin sheet made of a polyolefin-based resin or a polyester-based resin.

[0022] When using such a laminated sheet, the release sheet can be peeled off and the adhesive sheet can be attached to a transparent substrate such as window glass, and the visible information written on the surface of the self-adhesive layer, i.e., the adhesive surface, can be viewed through the substrate.

[0023] The method for producing the laminated sheet of the present invention includes, for example, the steps of preparing an adhesive sheet including a synthetic paper substrate and a self-adhesive layer, printing visible information on the surface of the release sheet that does not have a release agent layer (hereinafter, sometimes simply referred to as "release agent layer") including a silicone-based resin or a fluorine-based resin, and laminating the release sheet and the adhesive sheet so that the visible information printed surface of the release sheet faces the self-adhesive layer of the adhesive sheet. From the viewpoint of productivity, the step of preparing the adhesive sheet preferably includes the steps of applying a self-adhesive layer-forming composition to the surface of the synthetic paper substrate and crosslinking the self-adhesive layer-forming composition after foaming it.

[0024] By producing the laminated sheet in this manner, the visible information printed on the release sheet is clearly transferred to the surface of the self-adhesive layer in contact with it, and an adhesive sheet having visible information on the self-adhesive layer can be easily produced. The materials and formation methods of each layer constituting the laminated sheet are described below.

[0025] In the following description, the term "(meth)acrylic" refers to both acrylic and methacrylic. Similarly, the term "(meth)acryloyl" refers to both acryloyl and methacryloyl, and the term "(meth)acrylate" refers to both acrylate and methacrylate.

[0026] Furthermore, when a polymer "contains a monomer unit," it means that "the polymer contains repeating units derived from that monomer."

[0027] <Adhesive sheet> The adhesive sheet includes a synthetic paper substrate and a self-adhesive layer. The adhesive sheet may form the self-adhesive layer on the synthetic paper substrate via an optional layer, or may form the self-adhesive layer directly on the synthetic paper substrate. The self-adhesive layer is formed, for example, by foaming a specific composition for forming the self-adhesive layer and then crosslinking the foam.

[0028] <Synthetic paper base material> The substrate in the present invention uses a synthetic paper substrate. The synthetic paper substrate is not particularly limited as long as it is a substrate containing a thermoplastic resin, but may be, for example, a substrate formed by forming a film of a compound containing a thermoplastic resin, an inorganic fine powder and / or an organic filler. The synthetic paper substrate may be a porous sheet containing a thermoplastic resin. In addition, it is preferable to use a substrate formed by forming a compound containing the above-mentioned thermoplastic resin and, in addition to the filler, any other additives into a film. In addition, a known molding method can be used to form the compound into a film. As the synthetic paper substrate, for example, synthetic paper described in International Publication No. 2018 / 051984 can be used.

[0029] The thickness of the synthetic paper base material is preferably 20 to 900 μm, more preferably 30 to 800 μm. By making the thickness of the synthetic paper base material 20 μm or more, the mechanical strength of the entire laminated sheet of the present invention can be improved, and it becomes possible to form a large-area poster or the like. By making the thickness of the synthetic paper base material 900 μm or less, it is possible to prevent the entire laminated sheet of the present invention from becoming too stiff, and to reduce its own weight, thereby preventing it from falling off when applied.

[0030] <Self-adsorption layer> In the laminate of the present invention, the self-adhesive layer constituting a part of the adhesive sheet is formed, for example, by foaming a predetermined composition for forming the self-adhesive layer and then crosslinking it. The self-adhesive layer is preferably a foamed layer from the viewpoint of the adhesiveness to the adherend. The adhesive mode of the foamed layer is not glue adhesion, but adsorption to the adherend using fine pores. The foamed layer is easier to reattach than the conventional adhesive sheet using glue adhesion, and is suitable for use in applications such as wallpaper, posters, and stickers. In addition, in the case of glue adhesion, the release sheet laminated thereto often needs to have a release agent layer containing a silicone resin or a fluorine resin on its surface so that it can be easily peeled off by hand when the adhesive sheet is used. On the other hand, the self-adhesive layer, which is a foamed layer, does not need a release agent layer on the surface of the release sheet laminated thereto. Since a release sheet without a release agent layer can be printed on its surface, it is possible to print visible information on the surface of the release sheet and transfer it to the self-adhesive layer, as described below.

[0031] <<Composition for foam layer>> When the self-adhesive layer according to the present invention is a foam layer, the composition for forming the self-adhesive layer used to form the layer is called a "foam layer composition". The foam layer can be formed by crosslinking and foaming the foam layer composition. The foam layer composition contains the components described below and optionally further contains a solvent.

[0032] The foam layer according to the present invention is preferably a layer made of a resin composition containing an ethylene-vinyl acetate copolymer or a (meth)acrylic acid ester copolymer.

[0033] Ethylene-vinyl acetate copolymer is obtained by mixing ethylene and vinyl acetate in any ratio and polymerizing them. When the content of vinyl acetate monomer units contained in the ethylene-vinyl acetate copolymer is high, the adsorption power increases as the content of ethylene monomer units increases, and when the content of ethylene monomer units is high, the adsorption power increases as the content of vinyl acetate monomer units increases. The proportion of vinyl acetate monomer units in the ethylene-vinyl acetate copolymer is preferably 99% by mass or less, more preferably 95% by mass or less, even more preferably 90% by mass or less, and particularly preferably 85% by mass or less, while it is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more. If the proportion of vinyl acetate monomer units in the copolymer is 10% by mass or more and 99% by mass or less, the self-adhesive force of the laminated sheet can be sufficiently secured.

[0034] In the (meth)acrylic acid ester copolymer, examples of monomers constituting the repeating units thereof include, in addition to (meth)acrylic acid esters, α,β-unsaturated carboxylic acids, alkenyl aromatic compounds, vinyl cyanide compounds, olefin compounds, etc. These monomers may be used alone or in combination of two or more.

[0035] As the (meth)acrylic acid ester, from the viewpoint of increasing the flexibility of the laminate sheet and ensuring good self-adhesiveness, a (meth)acrylic acid alkyl ester is preferred, and a (meth)acrylic acid alkyl ester having an alkyl group of 1 to 14 carbon atoms (hereinafter sometimes abbreviated as "C1-14 (meth)acrylic acid alkyl ester") is more preferred.

[0036] Examples of C1-14 (meth)acrylic acid alkyl esters include methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, n-heptyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, n-octyl methacrylate, and n-dodecyl methacrylate. Among these, from the viewpoint of self-adhesiveness and cost, n-butyl acrylate, ethyl acrylate, and 2-ethylhexyl acrylate are preferred.

[0037] Examples of the α,β-unsaturated carboxylic acid include α,β-ethylenically unsaturated monocarboxylic acids such as acrylic acid and methacrylic acid, and α,β-ethylenically unsaturated polycarboxylic acids such as itaconic acid, maleic acid and fumaric acid, or acid anhydrides thereof. Among these, itaconic acid, acrylic acid and methacrylic acid are preferred, and acrylic acid is more preferred, from the viewpoints of reactivity with a crosslinking agent described below, stability of the polymer latex, and cost.

[0038] Examples of alkenyl aromatic compounds include styrene, α-methylstyrene, α-chlorostyrene, vinyltoluene, divinylbenzene, etc. Among these, styrene is preferred from the viewpoints of polymerizability and cost.

[0039] Examples of the vinyl cyanide compound include acrylonitrile, α-halogenoacrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile, α-alkylacrylonitrile such as methacrylonitrile and α-ethylacrylonitrile, etc. Among these, acrylonitrile is preferred from the viewpoint of improving the cohesive force of the foam layer composition and increasing the fracture strength of the foam layer.

[0040] In addition, the (meth)acrylic acid ester copolymer may have an N-methylol group. Specifically, any of the monomers constituting the (meth)acrylic acid ester copolymer may have an N-methylol group. By using a monomer having an N-methylol group, it becomes easier to set the gel fraction to a predetermined upper limit value or less, as described below, and as a result, it becomes easier to prepare a self-adhesive layer having appropriate self-adhesive force and excellent smoothness. Examples of monomers having an N-methylol group include, but are not limited to, N-methylol acrylamide and N-methylol methacrylamide. The above-mentioned monomers may be used alone or in combination of two or more kinds.

[0041] The proportion of (meth)acrylic acid ester monomer units in the (meth)acrylic acid ester copolymer is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, and preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less, based on the total repeating units (total monomer units) contained in the copolymer being 100% by mass. If the proportion of (meth)acrylic acid ester monomer units in the copolymer is 60% by mass or more, the self-adhesive strength of the laminated sheet can be sufficiently ensured. On the other hand, if the proportion of (meth)acrylic acid ester monomer units in the polymer is 99% by mass or less, the self-adhesive strength of the laminated sheet does not increase excessively, and the resin residue on the laminated sheet to be adhered can be suppressed.

[0042] The foam layer of the present invention is preferably a layer made of a resin composition containing a (meth)acrylic acid ester copolymer, since this allows good transfer of visible information using various printing inks, which will be described later.

[0043] <<Characteristics of copolymer>> [Glass transition temperature] The glass transition temperature of the copolymer is preferably -10°C or lower, more preferably -13°C or lower, even more preferably -17°C or lower, and particularly preferably -20°C or lower. If the glass transition temperature of the polymer is -10°C or lower, the laminate sheet can be well adhered to the adherend while the self-adhesive strength of the laminate sheet is sufficiently ensured, thereby preventing moisture from penetrating between the adherend and the laminate sheet. Therefore, the water resistance of the laminate sheet can be increased.

[0044] The lower limit of the glass transition temperature of the polymer is not particularly limited, but is preferably −40° C. or higher from the viewpoint of sufficiently suppressing the resin residue on the adherend of the laminated sheet. The glass transition temperature of the polymer can be measured using the method described in the examples of this specification.

[0045] [Gel fraction] The gel fraction of the copolymer is preferably 95% by mass or less, more preferably 93% by mass or less. If the gel fraction is 95% by mass or less, a foam layer and a laminated sheet having appropriate self-adhesive strength and excellent smoothness can be prepared. The lower limit of the gel fraction of the polymer is not particularly limited, but can be, for example, 50% by mass or more, and can be 70% by mass or more. The gel fraction of the polymer can be measured using the method described in the examples of this specification.

[0046] <<How to prepare the copolymer>> The polymerization method for obtaining the copolymer is not particularly limited, and may be any of solution polymerization, emulsion polymerization, suspension polymerization, bulk polymerization, etc., or other methods. There is no particular limit to the type or amount of polymerization initiator, emulsifier, dispersant, etc. used in the polymerization. There is no particular limit to the method of adding monomer, polymerization initiator, emulsifier, dispersant, etc. during polymerization. There is also no particular limit to the polymerization temperature, pressure, stirring conditions, etc.

[0047] The copolymer can be used in a solid state. However, when the copolymer is used in the form of a latex containing the copolymer (copolymer latex), such as a latex obtained by emulsion polymerization or a latex obtained by post-emulsification of the copolymer, the operation of mixing the copolymer with a crosslinking agent, a wax agent, etc. is easy, and the obtained composition for foaming layer is also conveniently foamed.

[0048] <<Crosslinking agent>> Since the self-adhesive layer of the present invention has suitable releasability from a release sheet that does not have a release agent layer containing a silicone-based resin or a fluorine-based resin, it is preferable that the ethylene-vinyl acetate copolymer and (meth)acrylic acid ester copolymer contained in the layer are crosslinked.

[0049] Examples of the crosslinking agent include carbodiimide-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, polyfunctional isocyanate-based crosslinking agents such as tolylene diisocyanate, trimethylolpropane tolylene diisocyanate, and diphenylmethane triisocyanate, metal salt-based crosslinking agents, metal chelate-based crosslinking agents, and peroxide-based crosslinking agents. Among these, epoxy-based crosslinking agents are preferably used, and compounds having two or more epoxy groups in one molecule are more preferably used. As the epoxy-based crosslinking agent, fatty acid polyglycidyl ether, glycerol polyglycidyl ether, and ethylene glycol diglycidyl ether are preferred.

[0050] The amount of the crosslinking agent in the foam layer composition is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of the copolymer described above. By having the amount of the crosslinking agent within the above-mentioned range, a foam layer that maintains appropriate strength and elasticity can be obtained. Therefore, when the pressure applied to the foam layer is released, the foam cells in the foam layer that have been crushed can recover to their original shape. In addition, the self-adhesive force of the laminate sheet can be ensured, and the resin residue on the laminate sheet's adherend can be sufficiently suppressed.

[0051] <<Wax agent>> The foam layer composition of the present invention may further contain a wax agent. The wax agent has the effect of adjusting the adsorption power of the foam layer containing the wax agent. It is presumed that the open cell structure and elasticity of the foam layer are improved by foaming and curing the foam layer composition containing the wax agent to form a foam layer, and the laminate sheet having the foam layer can have excellent air release properties after heating and pressing.

[0052] The wax agent may be a natural wax, a synthetic wax, or a mixture thereof, but in any case, it is preferable to use a wax agent containing a fatty acid ester, and more preferably a wax agent containing a fatty acid ester composed of a higher fatty acid having 16 or more carbon atoms and a higher alcohol having 30 or more carbon atoms.

[0053] The content of the fatty acid ester in the wax agent is preferably more than 50% by mass and not more than 100% by mass (i.e., the main component), preferably 70% by mass or more and not more than 100% by mass, more preferably 80% by mass or more and not more than 100% by mass, and particularly preferably 90% by mass or more and not more than 100% by mass, based on 100% by mass of the entire wax agent. The wax agent may contain one type of fatty acid ester, or may contain two or more types of fatty acid esters.

[0054] The amount of the wax agent in the foam layer composition is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 1.5 parts by mass or more, and preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the copolymer. If the amount of the wax agent is 0.5 parts by mass or more per 100 parts by mass of the copolymer, the air release property of the laminated sheet after heating and pressing can be further improved. On the other hand, if the amount of the wax agent is 10 parts by mass or less per 100 parts by mass of the copolymer, the obtained laminated sheet can be given good self-adhesive strength, and the air release property of the laminated sheet after heating and pressing can be further improved.

[0055] <<Solvent>> The solvent that may be optionally contained in the foam layer composition is not particularly limited, but is preferably water. When water is used as the solvent, the water contained in the foam layer composition may be, for example, water derived from the polymer latex.

[0056] <<Other ingredients>> The foam layer composition may optionally contain various additives to improve the processability in the manufacturing process of the foam layer and the laminate sheet and to improve the performance of the resulting foam layer and laminate sheet. For example, additives described in International Publication No. 2018 / 051984 can be used as such additives.

[0057] <<Characteristics of the foam layer>> The foam layer in the laminate sheet of the present invention is formed by crosslinking and foaming the above-mentioned composition for foam layer.

[0058] The density of the foam layer is not particularly limited, but is preferably 0.1 g / cm 3 It is preferable that the density of the foam layer is 0.1 g / cm3 or more and 0.8 g / cm3 or less, and more preferable that the density of the foam layer is 0.5 g / cm3 or more and 0.7 g / cm3 or less. If the density of the foam layer is 0.1 g / cm3 or more, the strength of the foam layer is ensured, and if the density of the foam layer is 1.0 g / cm3 or less, the air release property after heating and pressing of the laminated sheet is further improved while the resin remaining on the adherend can be sufficiently suppressed. The density of the foam layer can be calculated using the method described in the examples of this specification.

[0059] The thickness of the foam layer is preferably 0.03 mm or more, more preferably 0.05 mm or more, even more preferably 0.1 mm or more, and preferably 3 mm or less, more preferably 1 mm or less, even more preferably 0.5 mm or less, and particularly preferably 0.2 mm or less. If the thickness of the foam layer is 0.03 mm or more, the mechanical strength of the foam layer and the laminated sheet can be sufficiently ensured. On the other hand, if the thickness of the foam layer is 3 mm or less, the air release property of the laminated sheet after heating and pressing can be further improved. In addition, a laminated sheet having excellent repeated attachment properties (rework performance) can be obtained.

[0060] <Release sheet> The release sheet in the present invention is in direct contact with the self-adhesive layer, and is characterized in that it does not have a release agent layer containing a silicone-based resin or a fluorine-based resin on the surface on the self-adhesive layer side.

[0061] The release sheet is laminated on the surface of the self-adhesive layer to transfer visible information to the surface of the self-adhesive layer of the adhesive sheet and to prevent the adhesive sheet from adhering to any object other than the intended adherend. The release sheet is laminated on the self-adhesive layer to protect the layer until the adhesive sheet is used, and is separated from the self-adhesive layer and usually discarded when the adhesive sheet is used. Therefore, it is desired that the release sheet does not peel off easily during transportation of the laminated sheet or secondary processing such as printing, but can be easily peeled off by hand when the adhesive sheet is used.

[0062] From this viewpoint, in the laminate sheet of the present invention, the peel strength between the self-adhesive layer and the release sheet measured according to JIS K6854-2: 1999 is preferably 5 to 30 N / m, more preferably 5 to 20 N / m, even more preferably 5 to 15 N / m, and particularly preferably 5 to 12 N / m. If the peel strength is 5 N / m or more, the adhesive sheet and the release sheet do not easily peel off when the laminate sheet is subjected to secondary processing such as printing, and if the peel strength is 30 N / m or less, the two can be easily peeled off by hand.

[0063] The release sheet is preferably a sheet made of a thermoplastic resin, and is preferably a sheet made of a resin having low compatibility with the thermoplastic resin contained in the self-adhesive layer. For example, when the self-adhesive layer contains a (meth)acrylic acid ester copolymer, the release sheet is preferably a thermoplastic resin sheet made of a polyolefin resin such as a polyethylene resin or a polypropylene resin, or a polyester resin such as polyethylene terephthalate. In particular, from the viewpoint of good peel adhesion strength when attached to a self-adhesive layer containing a (meth)acrylic acid ester copolymer, it is preferable to use a sheet made of a non-polar polyolefin resin such as a polyethylene resin or a polypropylene resin, and it is preferable to use a sheet whose surface to be attached to the self-adhesive layer is relatively smooth.

[0064] As a result of further trial and error, it was found that a release sheet capable of achieving the desired peel adhesive strength is more likely to be obtained when the surface roughness of the above release sheet is within the range of preferably 0.01 to 1 μm, more preferably 0.02 to 0.5 μm, and even more preferably 0.03 to 0.3 μm, as defined in JIS B0601:2001.

[0065] On the other hand, the factor that prevents the release sheet constituting the laminate sheet of the present invention from easily peeling off during secondary processing such as printing of the laminate sheet is its resistance to stretching / ease of stretching against tensile stress. In order to make the adhesive sheet and release sheet constituting the laminate sheet of the present invention less likely to stretch, the tensile modulus of elasticity of both is preferably 100 to 5000 MPa, more preferably 200 to 4000 MPa.

[0066] The laminate sheet of the present invention can be printed on a synthetic paper substrate and used in the form of labels, POP displays, and the like.

[0067] To suppress curling during printing on the surface of a synthetic paper substrate, it is preferable that the adhesive sheet and the release sheet have approximately the same tensile modulus of elasticity. Specifically, it is preferable that the ratio of the tensile modulus of elasticity of the adhesive sheet and the release sheet constituting the laminated sheet, measured according to JIS K7161-1:2014, is within the range of 0.1 to 10. The tensile modulus ratio is more preferably within the range of 0.2 to 5, and even more preferably 0.3 to 3. If it is within the same range, peeling of the laminated sheet due to one-sided elongation is unlikely to occur.

[0068] <Visible Information> The laminate sheet according to the present invention has visible information on the surface of the self-adhesive layer on the release sheet side. The visible information can be visually recognized from the self-adhesive layer side through the adherend, particularly by attaching the adhesive sheet to a transparent adherend.

[0069] Here, the visible information is not particularly limited as long as it is visual information that can be seen and understood by the naked eye, but may include information indicating the manufacturer, country of manufacture, etc. of the person who produced the laminate sheet according to the present invention or the person who applied printing to the surface of the laminate sheet. For example, by making the synthetic paper base material and the release sheet opaque, the visible information may be used as a means for distinguishing the laminate sheet from a counterfeit product by confirming the manufacturer of the laminate sheet when the release sheet is peeled off during use.

[0070] (Laminated sheet manufacturing method) An example of a method for producing the laminate sheet of the present invention will now be described.

[0071] The laminated sheet of the present invention is manufactured by a method including, for example, a step of preparing an adhesive sheet having a synthetic paper base material and a self-adhesive layer (hereinafter referred to as the "adhesive sheet preparation step"), a step of printing visible information on the surface of the release sheet that does not have a release agent layer containing a silicone-based resin or a fluorine-based resin (hereinafter referred to as the "visible information printing step"), and a step of bonding the release sheet and the adhesive sheet so that the visible information printed surface of the release sheet faces the self-adhesive layer of the adhesive sheet (hereinafter referred to as the "printed surface bonding step").

[0072] After the adhesive sheet preparation step, the visible information printing step and the printed surface lamination step can be carried out at various times. Specific examples of the method for producing the laminated sheet of the present invention include the following methods.

[0073] Method 1) A long release sheet is printed with visible information on the side thereof that does not have a release agent layer containing a silicone resin or a fluorine resin, and the sheet is rolled up. After the adhesive sheet preparation process, the release sheet with the visible information printed thereon is unrolled and laminated so that the visible information printed side of the release sheet is in contact with the self-adhesive layer of the adhesive sheet, and the two are bonded together by being pressed between a pressure roller to obtain the laminated sheet of the present invention.

[0074] Method 2) After the adhesive sheet preparation step, the release sheet before printing the visible information is laminated on the self-adhesive surface of the adhesive sheet, and both are sandwiched and laminated by a pressure roller. At this time, the release sheet is laminated so that the surface of the release sheet that does not have a release agent layer containing a silicone resin or a fluorine resin faces the self-adhesive layer of the adhesive sheet. Next, the release sheet is once peeled off from the adhesive sheet, and visible information is printed on the surface of the release sheet that does not have a release agent layer containing a silicone resin or a fluorine resin, and then the release sheet is re-laid on the adhesive sheet so that the printed surface faces the self-adhesive layer, to obtain the laminated sheet of the present invention.

[0075] Method 3) After the adhesive sheet preparation step, the release sheet before printing the visible information is laminated on the self-adhesive surface of the adhesive sheet, and the two are sandwiched and laminated by a pressure roller. At this time, the release sheet is laminated so that the side of the release sheet that does not have a release agent layer containing a silicone resin or a fluorine resin faces the self-adhesive layer of the adhesive sheet. Then, cut and process to the desired size. The release sheet is peeled off from the processed laminate, and visible information is printed on the side that does not have a release agent layer containing a silicone resin or a fluorine resin, and then the printed side is re-laid on the adhesive sheet so that the printed side faces the self-adhesive layer, to obtain the laminate sheet of the present invention.

[0076] In any of the above methods, the visible information printed on the release sheet is transferred to the self-adhesive layer of the adhesive sheet, and an adhesive sheet having visible information on the surface of the self-adhesive layer and a laminated sheet including the same are obtained. For printing the visible information, inks with a fast drying speed are preferred, such as UV-curable inks and inks that dry and solidify by evaporation of a low-boiling point solvent, such as gravure inks. Among them, when an acrylic ink is used as the UV-curable ink and a urethane ink is used as the gravure ink, it is preferred that the transferability of the visible information is good when the foam layer is a layer made of a resin composition containing an ethylene-vinyl acetate copolymer or a (meth)acrylic acid ester copolymer. In particular, when the foam layer is a layer made of a resin composition containing a (meth)acrylic acid ester copolymer, the transferability is extremely good when these inks are used.

[0077] The method for printing visible information on the release sheet is not particularly limited, but typical examples include printing methods such as offset printing, flexographic printing, letterpress printing, and inkjet printing when UV ink is used, and gravure printing and letterpress printing when ink that dries by evaporation of a low boiling point solvent is used. From the viewpoint of production efficiency, the above method 1 is most preferable.

[0078] FIG. 1 shows a flow chart for explaining an example of a method for producing a laminate sheet of the present invention or a part thereof, method S10 (hereinafter, sometimes abbreviated as "production method S10"). As shown in FIG. 1, production method S10 includes a composition preparation step S1, a foaming step S2, a sheeting step S3, and a release sheet lamination step S4, in this order. Among these, steps S1 to S3 correspond to the above-mentioned "adhesive sheet preparation step", and step S4 corresponds to the above-mentioned "printed surface lamination step" in method 1, or the step of laminating the release sheet before visible information printing to the adhesive sheet in methods 2 and 3. Each step will be explained below.

[0079] <Composition preparation step S1> The composition preparation step S1 is a step of preparing a composition for forming a self-adhesive layer, specifically, a step of preparing a composition for a foam layer when the self-adhesive layer is a foam layer.

[0080] Specifically, in the composition preparation step S1, a composition for a foam layer can be prepared by mixing, by any method, an ethylene-vinyl acetate copolymer or a (meth)acrylic acid ester copolymer, a crosslinking agent, a wax agent, etc., and optionally a solvent and other additives.

[0081] For example, when a polymer latex is used to prepare the foam layer composition, a crosslinking agent, a wax agent and other additives may be added to the polymer latex and mixed by a known method.

[0082] In addition, when a solid polymer is used without using a solvent to prepare the composition for the foam layer, the solid polymer, the crosslinking agent, the wax agent and other additives may be mixed by a known method (for example, using a known roll, Henschel mixer, kneader, etc.).

[0083] Here, the viscosity of the foam layer composition containing a solvent (e.g., in the form of an emulsion or dispersion) is preferably 1,000 mPa·s to 10,000 mPa·s, more preferably 2,000 mPa·s to 10,000 mPa·s, and even more preferably 3,500 mPa·s to 5,500 mPa·s. If the viscosity of the foam layer composition is 1,000 mPa·s or more, it is possible to prevent dripping and difficulty in controlling the thickness when a foam formed from the foam layer composition is coated on a substrate to form a foam layer. On the other hand, if the viscosity of the foam layer composition is 10,000 mPa·s or less, it is also possible to prevent difficulty in controlling the expansion ratio by mechanical foaming when forming a foam layer.

[0084] The viscosity of the foam layer composition can be measured by the method described in the Examples of this specification.

[0085] <Foaming process S2> The foaming step S2 is a step of foaming the composition for foam layer to obtain a foam of the composition for foam layer.

[0086] Specifically, in the foaming step S2, the foaming layer composition prepared in the composition preparation step S1 is foamed to obtain a foam in an unsolidified (uncrosslinked) state. When the foaming layer composition is in the form of an emulsion or dispersion, a foamed emulsion or foamed dispersion is obtained.

[0087] Mechanical foaming is usually used as the foaming method. The foaming ratio may be adjusted as appropriate, but is usually 1.2 to 5 times, preferably 1.5 to 4 times. The mechanical foaming method is not particularly limited, but can be carried out by mixing a certain amount of air into the emulsion or dispersion of the foam layer composition and stirring it continuously or batchwise with an oak mixer, whipper, or the like. The foamed emulsion or foamed dispersion thus obtained is creamy.

[0088] By forming pores by the mechanical foaming, a foamed layer having excellent air escape properties can be obtained through a sheet forming step S3 described later. When the foaming ratio is 1.2 times or more, the air escape properties can be prevented from decreasing, and when the foaming ratio is 5 times or less, the strength of the foamed layer can be prevented from decreasing.

[0089] <Sheeting process S3> The sheet forming step S3 is a step of forming the foam into a sheet shape and then carrying out a crosslinking reaction of the foam to produce a foam layer.

[0090] In the sheet forming step S3, the method for forming the foam produced in the foaming step S2 into a sheet is not particularly limited. A suitable method is, for example, a method in which the foam is coated on a desired synthetic paper base material and formed into a sheet. In this way, by coating the foam on the desired synthetic paper base material and allowing the crosslinking reaction to proceed, a laminated sheet in which a foam layer is provided directly on the synthetic paper base material can be obtained.

[0091] To coat the foam onto the synthetic paper substrate, a commonly known coating device such as an applicator, a bar coater, a roll coater, a reverse roll coater, a screen coater, a doctor knife coater, or a comma knife coater can be used.

[0092] A method for crosslinking a foam coated in a sheet form on a synthetic paper substrate or the like is preferably a method for heating and drying the foam. The heating and drying method is not particularly limited as long as it is a method capable of drying and crosslinking a foam coated on a synthetic paper substrate or the like, and a known drying oven (for example, a hot air circulation type oven, a hot oil circulation hot air chamber, a far infrared heater chamber) can be used. The drying temperature can be, for example, 60°C or higher and 180°C or lower. In addition, it is preferable to perform multi-stage drying such that drying is performed from the inside at a low temperature in the early stage of drying and is sufficiently dried at a higher temperature in the later stage of drying, rather than performing drying at a constant temperature.

[0093] The properties (density, thickness, hardness, etc.) of the foam layer can be adjusted, for example, by changing the mixing ratio of air bubbles, the composition of the foam layer composition, the solids concentration, the drying and crosslinking conditions, etc.

[0094] <Release sheet lamination process S4> The release sheet lamination step S4 is a step of laminating the self-adhesive layer (foam layer) so that the side of the release sheet that does not have a release agent layer containing a silicone resin or a fluorine resin is in contact with the self-adhesive layer (foam layer). Specifically, after the adsorption layer formed into a sheet shape by coating in the sheet forming step S3 is heated and dried, a long release sheet is unwound and laminated so that the self-adhesive layer on the synthetic paper base material and the corresponding side of the release sheet are in contact with each other, and then the two are sandwiched and bonded together using a pressure roller.

[0095] In the case of the above-mentioned method 1, the release sheet used here has visible information printed thereon in advance in a "visible information printing step" outside the manufacturing method S10, so that the laminated sheet of the present invention can be obtained in step S4.

[0096] In the case of the above-mentioned method 2, the adhesive sheet and the release sheet are once laminated in step S4, and then the release sheet is peeled off. Subsequently, visible information is printed on the surface of the release sheet either online or offline, and then the self-adhesive layer of the adhesive sheet is re-laminated to obtain the laminated sheet of the present invention.

[0097] The laminated sheet obtained by the release sheet lamination step S4 or the subsequent release sheet peeling and re-laminating step (in the case of method 2) is usually wound up by a winder and cut by a press cutter, a slitter, or the like into a convenient size.

[0098] In the case of the above-mentioned method 3, the adhesive sheet and the release sheet before printing the visible information are laminated in the above-mentioned step S4, and then the laminate is wound up by a winder, cut, and processed into a desired size, and the release sheet is peeled off from the laminate. After printing visible information on the surface of the peeled release sheet, the laminate is re-laid on the self-adhesive layer of the adhesive sheet, thereby obtaining the laminate sheet of the present invention.

[0099] The "laminate sheet" in the present invention includes both a long sheet before cutting and a sheet processed to a desired size by cutting.

[0100] <Applications of laminated sheets> The synthetic paper base surface of the laminate sheet of the present invention can be printed using, for example, offset printing, seal printing, flexographic printing, silk screen printing, gravure printing, laser printers, thermal transfer printers, inkjet printers, and the like.

[0101] The laminate sheet having printing applied to the synthetic paper base surface can be advantageously used for outdoor applications such as sales promotion cards, so-called POP cards (posters, stickers, displays, etc.), gardening POP (inserted labels, etc.), road signs (funerals, home exhibitions, etc.), signboards (no entry, forest road work, etc.), etc. The laminate sheet of the present invention is preferable because visible information is also printed on the self-adhesive layer surface of the adhesive sheet, and therefore, by adhering it to a particularly transparent adherend, the visible information on the adhesive layer side can be seen through the adherend.

[0102] The laminate sheet of the present invention can also be used to determine the authenticity of the sheet itself by, for example, writing the manufacturer's name or product name on the surface of the self-adhesive layer.

[0103] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%" and "parts" expressing amounts are by mass unless otherwise specified.

[0104] In addition, in a polymer produced by polymerizing a plurality of types of monomers, the ratio of a monomer unit formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of the certain monomer to the total monomers used in the polymerization of the polymer, unless otherwise specified. In the examples and comparative examples, the glass transition temperature and gel fraction of the polymer, the viscosity of the foam layer composition, the density of the foam layer, the transferability of visible information in the laminate sheet, and the adsorption of the adhesive sheet were evaluated by the following methods.

[0105] <Glass transition temperature of polymer> The glass transition temperature (Tg) of the polymer used as the material of the self-adhesive foam layer (hereinafter simply referred to as the "foam layer") was measured by the following method. A polymer latex containing a polymer was applied to a polyethylene terephthalate film having a thickness of 50 μm with a 250 μm applicator, and dried at room temperature for 24 hours to obtain a film formed on the polyethylene terephthalate film. The glass transition temperature (°C) of the film formed on the polyethylene terephthalate film (other than the polyethylene terephthalate film) was measured as a sample according to JIS K 7121 using a differential scanning calorimeter (DSC7000X manufactured by Hitachi High-Tech Science Corporation) under the conditions of a measurement temperature of -50°C or more and 160°C or less, and a heating rate of 10°C / min.

[0106] <Gel fraction of polymer> The gel fraction of the polymer used as the material of the foam layer was measured by the following method. The polymer was applied to a polyethylene terephthalate (PET) film having a thickness of 50 μm using a 250 μm applicator, and dried at room temperature for 24 hours to obtain a resin film. A predetermined amount (X) (about 500 mg) of this film was precisely weighed as a sample, and this was immersed in 100 ml of ethyl acetate at room temperature for 3 days, after which the insoluble matter was filtered through a 200 mesh wire net, air-dried at room temperature for 15 hours, then dried at 100° C. for 2 hours, cooled at room temperature, and the weight (Y) of the sample was measured. The gel fraction was calculated by substituting X and Y into the following formula. Gel fraction (%)=(Y) / (X)×100

[0107] <Viscosity of the foam layer composition> The viscosity of the foam layer composition was measured at 23° C. using a Brookfield viscometer (manufactured by Rion Corporation, "VISCOTESTER VT-06").

[0108] <Density of foam layer> After preparing the adhesive sheet, a test piece was cut to a size of 20 cm x 20 cm to prepare it. The mass of the cut test piece: Xg was precisely weighed, and the mass of the substrate cut to 20 cm x 20 cm: Yg was precisely weighed. Thereafter, the thicknesses of the prepared adhesive sheet and substrate were measured with a thickness gauge, and the thickness of the substrate was subtracted from the thickness of the adhesive sheet to obtain the thickness of the foam layer: Tcm. At this time, the thickness value was calculated from the average value of measurements taken at six points. The density of the foam layer was calculated by substituting the measured values ​​of X, Y, and T into the following formula. Density (g / cm 3 )=(XY) / (T×20×20)

[0109] <Transferability of visible information> A laminated sheet was prepared and kept at room temperature for one week. The release sheet was then peeled off from the laminated sheet, and the foam layer surface of the adhesive sheet was attached to a glass plate. The visible information transferred to the foam layer was visually observed through the glass plate and evaluated. If the ink was not sufficiently transferred from the release sheet surface to the foam layer surface and the color of the visible information was faint, the visible information may not be visible depending on the viewing angle relative to the foam layer surface.

[0110] <Adhesive sheet adhesive properties> In the evaluation, the adhesive sheet attached to the glass plate was left as it was at room temperature for one week, and then the state of adhesion of the adhesive sheet was observed and evaluated.

[0111] Example 1 <Preparing the release sheet> The design shown in Figure 2 was printed on the entire surface of the corona-discharge-treated side of a biaxially oriented polypropylene film (FOS60, manufactured by Futamura Chemical Co., Ltd.) with a urethane-based gravure ink (Rio Alpha S R92H Sumi AN, manufactured by Toyo Ink Co., Ltd.) using a gravure printing machine (manufactured by Orient Sogyo Co., Ltd.). The print was dried for 5 seconds in an oven at 100°C to obtain a release sheet with visible information. The ink transfer from the printing plate to the release sheet was good, and the ink was not repelled by the surface of the release sheet, resulting in a clear design.

[0112] <Preparation of Polymer> A monomer mixture consisting of 64 parts of ethyl acrylate, 12 parts of 2-ethylhexyl acrylate, 12 parts of n-butyl acrylate, 9 parts of acrylonitrile, 2 parts of styrene and 1 part of acrylic acid, and 0.4 parts of sodium polyoxyethylene alkyl sulfate (Kao Corporation, Latemul E-118B) were mixed and stirred into 27.0 parts of deionized water to obtain a monomer emulsion.

[0113] Next, a glass reaction vessel equipped with a reflux condenser, a dropping funnel, a thermometer, a nitrogen inlet, and a stirrer was prepared separately from the above, and 43.0 parts of deionized water and 0.2 parts of sodium polyoxyethylene alkyl sulfate were placed in this glass reaction vessel, and the temperature was raised to 80°C while stirring. Then, while maintaining the temperature at 80°C, 0.3 parts of ammonium persulfate dissolved in 5.7 parts of deionized water was added, and then the monomer emulsion obtained above was gradually added over 4 hours. After the addition was completed, stirring was continued for another 4 hours, and then the reaction was terminated by cooling to obtain a reaction mixture. The polymerization conversion rate at this time was almost 100% (98% or more), and the resulting reaction mixture was adjusted to pH 5.0 with 5% ammonia water, and 2.5 parts of polyoxyethylene lauryl ether (manufactured by Kao Corporation: Emulgen 120) was added, followed by concentration to obtain a polymer latex with a solid content concentration of 55%. The polymer contained in the obtained polymer latex had a glass transition temperature of -26°C and a gel fraction of 91%.

[0114] <Preparation of Foam Layer Composition> In a mixing vessel, 100 parts of the polymer latex (i.e., 55 parts of the polymer contained in the polymer latex) in terms of solid content, 3 parts (5.5 parts per 100 parts of polymer) of an epoxy-based crosslinking agent [fatty acid polyglycidyl ether (Japan Coating Resin Co., Ltd., Ricabond EX-8)], 2 parts (3.6 parts per 100 parts of polymer) of a wax agent (containing a fatty acid ester having a fatty acid moiety with a carbon number of 16 to 34), and 4 parts of a foam stabilizer [ammonium stearate (San Nopco Co., Ltd., Nopco DC-100A)] were added in this order. Finally, a thickener [sodium polyacrylate (Toagosei Co., Ltd., Aron A-20L)] was added to adjust the viscosity to 4250 mPa·s, thereby obtaining a foam layer composition.

[0115] <Preparation of synthetic paper substrate> Propylene homopolymer (Novatec PP:MA4, Japan Polychem Corporation) 74%, high density polyethylene (Novatec HD:HJ360, Japan Polychem Corporation) 10%, and calcium carbonate (Softon 1800, Bihoku Funka Kogyo Co., Ltd.) 16% were melt-kneaded at 250°C, fed into a die set at 250°C, extruded into a sheet, and cooled with a cooling roll to obtain an unstretched sheet. The unstretched sheet obtained was heated to 135°C and stretched 4 times in the machine direction to obtain the base layer (b).

[0116] Next, 52% propylene homopolymer (Novatec PP: EA8, manufactured by Japan Polychem Corporation), 3% high density polyethylene (Novatec HD: HJ360, manufactured by Japan Polychem Corporation), and 45% calcium carbonate (Softon 1800, manufactured by Bihoku Funka Kogyo Co., Ltd.) were melt-kneaded at 250°C in separate extruders, and then fed into a die set at 250°C and extruded into a sheet. The sheet was laminated on both sides of the above-mentioned base layer (b) as the surface layer (a) and back layer (c), and cooled to 60°C to obtain a three-layer laminate film (a / b / c).

[0117] The resulting three-layer laminate film was heated again to 180°C and stretched 9 times in the transverse direction using a tenter, then annealed at 160°C, cooled to 60°C, and the edges were slit to obtain a synthetic paper substrate made of a multilayered resin stretched film.

[0118] <Preparation of laminated sheet> The foam layer composition obtained as described above was stirred with a whisk until the foaming ratio reached 1.6 times, and the stirring speed was further reduced and stirring was continued for 5 minutes.

[0119] The foamed foam layer composition (foam) was coated on the above-mentioned synthetic paper substrate using a 0.3 mm applicator. This was placed in a drying oven and held at 80°C for 1.33 minutes, 120°C for 1.33 minutes, and 140°C for 1.33 minutes to dry and crosslink the foam layer and prepare an adhesive sheet. Next, the previously prepared release sheet was laminated so that the printed surface was in contact with the foam layer of the adhesive sheet to obtain a laminated sheet. The thickness of the foam layer after drying was 0.133 mm.

[0120] <Evaluation> The release sheet was peeled off from the resulting laminated sheet, and the foam layer surface of the adhesive sheet was attached to a glass plate. When the <transferability of visible information> was evaluated using the method described above, the visible information observed visually through the glass plate was clearly readable from any angle. In addition, when the <adhesive sheet's adhesiveness> was evaluated using the method described above, no lifting or peeling occurred, and the adhesive sheet was in close contact with the glass plate, just like when it was attached.

[0121] Example 2 A laminate sheet was obtained in the same manner as in Example 1, except that the following foam layer composition was used.

[0122] <Preparation of Polymer> A polymer latex was obtained in the same manner as in Example 1, except that 46.9 parts of ethyl acrylate, 45.8 parts of butyl acrylate, 5.9 parts of acrylonitrile, and 1.4 parts of N-methylolacrylamide were used as monomers. The glass transition temperature of the polymer contained in the obtained polymer latex was −25.9° C., and the gel fraction was 43.1%.

[0123] <Preparation of Foam Layer Composition> In a mixing vessel, 100 parts of the polymer latex (polymer latex contains 55 parts of polymer) in terms of solid content, 3.6 parts of a carbodiimide crosslinking agent (DIC, DICNAL HX) in terms of solid content, and 4.2 parts of titanium oxide water dispersion (DIC, DISOERSE WHITE HG-701) in terms of solid content were added and stirred with a high-speed disperser. Next, while continuing stirring, 2 parts of a thickener (carboxylic acid modified acrylic acid ester polymer. Toa Gosei, Aron B-300K) in terms of solid content, and 4.1 parts of a foam stabilizer [a 1 / 1 mixture of alkyl betaine amphoteric acid / fatty acid alkanolamide mixture (DIC, DICNAL M-20) / sulfonic acid type anionic surfactant (DIC, DICNAL M-40) in terms of solid content] were added in this order, mixed uniformly, and then filtered through a 150 mesh stainless steel sieve. Finally, ammonia was added to adjust the viscosity to 4,500 mPa·s to obtain a foam layer composition.

[0124] <Evaluation> The release sheet was peeled off from the resulting laminated sheet, and the foam layer surface of the adhesive sheet was attached to a glass plate. When the <transferability of visible information> was evaluated using the method described above, the visible information observed visually through the glass plate was clearly readable from any angle. In addition, when the <adhesive sheet's adhesiveness> was evaluated using the method described above, no lifting or peeling occurred, and the adhesive sheet was in close contact with the glass plate, just like when it was attached.

[0125] Example 3 A surface-treated surface of a biaxially oriented polypropylene film (FOS60 manufactured by Futamura Chemical Co., Ltd.) having one side subjected to a corona discharge surface treatment was laminated as a temporary release sheet on the foam layer surface of the adhesive sheet prepared in the same manner as in Example 1.

[0126] Next, using a lamination machine, the temporary release sheet was peeled off from the adhesive sheet, and a release sheet prepared by the method described below was laminated on the adhesive sheet with its printed surface facing the foam layer, to obtain a laminated sheet.

[0127] <Preparing the release sheet> The design shown in Figure 2 was printed on the entire surface of a biaxially oriented polypropylene film (FOS60, manufactured by Futamura Chemical Co., Ltd.) that had been subjected to a corona discharge surface treatment on one side, using an acrylic UV-curable ink (UV Flexo 500 indigo, manufactured by T&K YOKA Co., Ltd.) with a flexographic printing machine (manufactured by Taiyo Kikai Co., Ltd.). A metal halide lamp was used to print the design shown in Figure 2 on the corona discharge treated surface. 2 The ink was hardened by UV irradiation at a dose of 1000 x 1000 x 1000, yielding a release sheet with visible information. The ink was transferred well from the printing plate to the release sheet, and the ink was not repelled by the surface of the release sheet, resulting in a clear pattern.

[0128] <Evaluation> The release sheet was peeled off from the resulting laminated sheet, and the foam layer surface of the adhesive sheet was attached to a glass plate. When the <transferability of visible information> was evaluated using the method described above, the visible information observed visually through the glass plate was clearly readable from any angle. In addition, when the <adhesive sheet's adhesiveness> was evaluated using the method described above, no lifting or peeling occurred, and the adhesive sheet was in close contact with the glass plate, just like when it was attached.

[0129] Example 4 A laminate sheet was obtained in the same manner as in Example 3, except that a release sheet prepared by the following method was used.

[0130] <Preparing the release sheet> The design shown in Figure 2 was printed on the entire surface of the corona-discharge-treated side of a biaxially oriented polypropylene film (FOS60, manufactured by Futamura Chemical Co., Ltd.) with an acrylic UV-curable ink (UV161 indigo, manufactured by T&K YOKA Co., Ltd.) using a letterpress printing machine (manufactured by Sanki Kikai Co., Ltd.). A metal halide lamp was used to print the design at 30 mJ / cm. 2 The ink was cured to obtain a release sheet having visible information.

[0131] Comparative Example 1 A release sheet was prepared in the same manner as in Example 1, except that a silicone-coated film (60RL-01, manufactured by Oji F-Tex Co., Ltd.) was used instead of the biaxially oriented polypropylene film with a corona discharge surface treatment on one side. Since the ink was repelled by the surface of the silicone-coated film, the ink was not transferred sufficiently from the printing plate to the release sheet, and the printed design was unclear.

[0132] A laminate sheet was produced in the same manner as in Example 1 using the obtained release sheet.

[0133] <Evaluation> The release sheet was peeled off from the obtained laminated sheet, and the foam layer surface of the adhesive sheet was attached to a glass plate. When the <transferability of visible information> was evaluated using the method described above, the visible information observed visually through the glass plate was almost unreadable. In addition, when the <adhesive sheet's adhesiveness> was evaluated using the method described above, no lifting or peeling occurred, and the adhesive sheet was in close contact with the glass plate, just as when it was attached. [Explanation of symbols]

[0134] S1 Composition preparation process S2 Foaming process S3 Sheeting process S4 Release sheet lamination process

Claims

1. A laminated sheet comprising an adhesive sheet including a synthetic paper base material and a self-adhesive layer, and a release sheet, wherein the self-adhesive layer and the release sheet are in direct contact with each other, the release sheet does not have a release agent layer containing a silicone-based resin or a fluorine-based resin on the surface facing the self-adhesive layer, and the self-adhesive layer is configured to have visible information on the surface facing the release sheet.

2. The laminated sheet according to claim 1 , wherein the self-adhesive layer is a foam layer.

3. The laminate sheet according to claim 2, wherein the foam layer comprises an ethylene-vinyl acetate copolymer or a (meth)acrylic acid ester copolymer.

4. 4. The laminate sheet according to claim 1, wherein the release sheet is a thermoplastic resin sheet made of a polyolefin resin or a polyester resin.

5. preparing an adhesive sheet comprising a synthetic paper substrate and a self-adhesive layer; printing visible information on the surface of the release sheet that does not have a release agent layer containing a silicone-based resin or a fluorine-based resin; A method for manufacturing a laminated sheet, comprising a step of bonding the release sheet and the adhesive sheet so that the visible information printed surface of the release sheet faces the self-adhesive layer of the adhesive sheet, thereby transferring visible information to the self-adhesive layer.

6. The step of preparing the adhesive sheet comprises: applying a self-adhesive layer-forming composition to a surface of the synthetic paper base material; and a step of crosslinking the self-adhesive layer-forming composition after foaming the composition. The method according to claim 5 .

Citation Information

Patent Citations

  • Time division exchange system

    JP1982052292A

  • Pressure-sensitive adhesive sheet with multicolor pattern and preparation thereof

    JP1992085383A

  • Adhesive laminate and manufacturing method of the same

    JP2017062430A

  • Adhesive sheet and article

    JP2021095547A

  • Self-adsorbable foamed laminate sheet and composition for self-adsorbable foamed sheet

    WO2018151274A1